Analysing the nature and characteristics of the nursing agency industry in South Africa - Olojede, Omolola Iwayemi (My University, 2013)
Background The aim of this study was to describe the nature and characteristics of nursing agencies and their implications for the South African health care system. Methods A mixed method study was used that included in-depth interviews with six key informants and a telephone survey of 106 nursing agencies. Results The majority of agencies (76.9%) were established between 2000 and 2009; reported formal contracts with their clients (77%) and a code of conduct (97.9%). They mainly service private patients (45.1%) and old age homes (27.4%). Between 5.7% and 67.4% of agencies provide non-financial benefits to casual health workers. The main challenge is reported gaps in the regulation and monitoring of the industry. Conclusion There is need for tighter regulation and monitoring of nursing agencies in the health sector, in order to ensure that casual health workers are not exploited, while meeting the care needs of clients in old-age and